Evaluation of Beauveria bassiana for Monalonion velezangeli (Hemiptera: Miridae) control in coffee crop. (2020)
Monalonion velezangeli (Hemiptera: Miridae) is a polyphagous pest found in Colombia which attacks ornamentals, weeds, timber and fruit trees including coffee. The pathogenicity of Beauveria bassiana strain B at 1 x 107 conidia/ml was evaluated on Monalonion velezangeli by immersion. The fungus caused 84 % mortality on the insect. Cissus verticillata plants were infested with M. velezangeli and applications of the fungus at 4 x 1010 conidium/L were done. Average insects mortality treated with the fungus was 84 %. Under field conditions, in the department of Huila, in a coffee plot infested with M. velezangeli the following treatment were applied: strain B at 4 x 1010 conidium/L, insecticide Chlorpyrifos at 4 cc/L and water. In a first assay, groups of nine trees (20 repetitions) were chosen. Both the insecticides and the fungus caused insect mortality with an 80 to 90 % decrease in the percentage of trees with new damage. Meanwhile the decrease in the control was 40 %. In a second assay, three plots of 450 trees were selected and the same treatments were applied. Percentage of trees affected in the control ranged between 19 and 11 %. The plot in which the insecticide was applied, started with an infestation of 29 %, and at the end of the assay the infestation was 20 % and the highest damage was observed in this plot. In the plot where B. bassiana was applied the initial infestation was 30 % and at the end of the assay, this plot showed the lowest infestation level near to 5 %. The B. bassiana strain B becomes a feasible alternative for M. velezangeli pest control on coffee plantations.